Exploring interactions between farmgate, markets, and consumers: Initial insights from a high-frequency integrated market survey in Bangladesh - Kabir, A.N.M. Faijul; Cheesman, Stephanie; Chowdhury, Samira; Ahmed, Sharif; Miajy, Abu Abdullah; Ali, Md. Jahangir; Islam, Md. Saiful; Kurishi, Alanuzzaman; Krupnik, Timothy J.; Veettil, Prakashan Chellattan (TAFSSA, 2023)
This research note presents initial findings from a high-frequency market survey conducted in four districts of Northern Bangladesh. The survey examines price fluctuations from farmgate to market, food production diversification, and consumer dietary choices from August to October 2023 in the Rajshahi, Chapai Nawabganj, Rangpur, and Dinajpur Districts, which are part of TAFSSA's learning landscape locations. High-frequency data collection has occurred biweekly six times thus far and continues. Future analyses and research will delve into price transformations following the sale of diversified crops in which farmers are participating in experiments. This research note is based on six rounds of data collection and offers preliminary insights into how farmers contribute to and benefit from a sustainable food supply chain in these regions.